Cathodic delamination kinetics of thin polystyrene model coatings bound to zinc via organosilanes. Issue 3 (15th October 2018) - Iqbal, Danish; Rechmann, Julian; Bashir, Asif; Sarfraz, Adnan; Altin, Abdulrahman; Erbe, Andreas
Abstract : The cathodic delamination of poly(styrene) [PS] model coatings from oxide‐covered zinc has been evaluated by scanning Kelvin probe (SKP). Linear and acrylate cross‐linked PS model coatings covalently bound to zinc oxide via ZnOSi bonds have been prepared. PS was prepared by thermally initiated free radical polymerization in the presence of vinyltrimethoxy silane modified zinc. Cross‐linkers ethylene glycol diacrylate (EDA) and hexanediol diacrylate (HDA) were used in some preparations. Resulting polymers are 8–15 nm thick. PS model coatings show a delamination rate of only ≈20% of that of comparable poly(methyl methacrylate) [PMMA] samples. The slower cathodic delamination of PS is attributed to denser chain packing and higher amounts of hydrophobic moieties, leading to a reduction in penetration of corrosive species. As opposed to the situation in PMMA, the addition of HDA increases the delamination rate, due to its flexible chains and hydrophilic groups. The lowest delamination rate is observed in the presence of 25% EDA. Consequently, ester hydrolysis of acrylates accelerates delamination, it is however not the main factor in cathodic delamination of such thin model system. Abstract : Ultrathin, hydrophobic poly(styrene) model coatings have been prepared to investigate their cathodic delamination behavior. The densly packed poly(styrene) delaminates slow, however, acrylate crosslinking increases the delamination rate.